(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the role of audiovisual input, especially movies and TV series, in English vocabulary learning. Vocabulary acquisition is one of the essential components of foreign language education, since learners need a sufficient number of words and expressions to understand speech, read texts, write coherently and communicate effectively. Movies and TV series provide students with authentic language, natural pronunciation, contextualized vocabulary, visual support and cultural information. The article analyzes how audiovisual input supports vocabulary development through repeated exposure, incidental learning, subtitle use, contextual guessing and emotional involvement. It also discusses methodological ways of using films and series in English lessons, including pre-viewing, while-viewing and post-viewing activities. The study concludes that movies and TV series can be effective supplementary tools for vocabulary learning if they are selected according to students’ level and used with purposeful learning tasks.